2022
DOI: 10.21125/edulearn.2022.0626
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Advantages/Difficulties of Remote Teaching During Covid-19 Pandemic: Results From a Survey With 3000 Italian Engineering Students

Abstract: On 11 th March 2020, the Director-General of The World Health Organization declared COVID-19 a pandemic. From this date, in Italy as in most parts of the world, life dramatically changed in many aspects: smart working and remote teaching became familiar words, while students and teachers at all educational levels, from primary school to university, had to face sudden changes and new challenges. Emergency remote teaching became widespread, and new methodologies to deliver classes and courses were adopted by edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Question 11 was scored negatively by almost 2500 students, while questions 2 and 3 were both scored positively by about 2000 students. The mean values and the medians for questions 2, 3, and 11, as in [30], confirmed these significant differences, while, in general, we observed that the mean value for the items overall was just below the neutral value of "3/5" on the Likert scale that was used in the questionnaire.…”
Section: Remote Teaching (Rt)supporting
confidence: 72%
See 2 more Smart Citations
“…Question 11 was scored negatively by almost 2500 students, while questions 2 and 3 were both scored positively by about 2000 students. The mean values and the medians for questions 2, 3, and 11, as in [30], confirmed these significant differences, while, in general, we observed that the mean value for the items overall was just below the neutral value of "3/5" on the Likert scale that was used in the questionnaire.…”
Section: Remote Teaching (Rt)supporting
confidence: 72%
“…At first glance, three clear higher bars can be observed in the two histograms. Question 11 was scored negatively by almost 2500 students, while questions 2 and 3 were both Table 2 shows the mean value, the standard deviation, and the median referring to all the questions from 2 to 14, as we computed in a previous work [30]. At first glance, three clear higher bars can be observed in the two histograms.…”
Section: Remote Teaching (Rt)mentioning
confidence: 81%
See 1 more Smart Citation
“…To investigate the learners' opinion about ERT and its effects on these students, we adopted a survey method and created an ad-hoc questionnaire which was administered online in July 2021, at the end of the second term of the academic year 2020-2021. Submitted to both Politecnico di Milano bachelor students (B) and master's students (Ma), this questionnaire consisted of 66 items pertaining to 6 different constructs, as illustrated with more detail in previous studies (Mazzola et al, 2022(Mazzola et al, , 2023. The overall number of learners enrolled on Architecture, Design and Engineering who participated voluntarily in this survey, was 3,920 and they gave explicit consent to use the collected data for research purposes.…”
Section: Materials and Methods Research Designmentioning
confidence: 99%
“…To investigate the learners' opinion about ERT and its effects on these students, we adopted a survey method and created an ad-hoc questionnaire which was administered online in July 2021, at the end of the second term of the academic year 2020-2021. Submitted to both Politecnico di Milano bachelor students (B) and master's students (Ma), this questionnaire consisted of 66 items pertaining to 6 different constructs, as illustrated with more detail in previous studies (Mazzola et al, 2022(Mazzola et al, , 2023. The overall number of learners enrolled on Architecture, Design and Engineering who participated voluntarily in this survey, was 3,920 and they gave explicit consent to use the collected data for research purposes.…”
Section: Materials and Methods Research Designmentioning
confidence: 99%